Botulinum neurotoxin for the treatment of blepharospasm, cervical dystonia, adult spasticity, and headache: Payment policy perspectives. Issue 3 (June 2016) - Govindarajan, Raghav; Shepard, Katie M.; Moschonas, Constantine; Chen, Jack J.
Abstract : Abstract: This article is presented as a companion to the American Academy of Neurology guideline update on the use of botulinum neurotoxin (BoNT) for the treatment of blepharospasm, cervical dystonia, adult spasticity, and headache. Whereas the guideline update provides clarity on the efficacy of different BoNT-branded preparations for the 4 listed indications, this companion piece identifies ambiguities in the evidence for efficacy among various brand names for a given clinical indication, their dosing equivalencies, as well as different clinical indications. This article provides guidance and background information to reduce obstacles for third party payment, especially when uncertainties exist and levels of evidence are lower.